2020
DOI: 10.3892/ijmm.2020.4563
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane reduces intracellular survival of Staphylococcus aureus in macrophages through inhibition of JNK and p38 MAPK‑induced inflammation

Abstract: Macrophages are active contributors to the innate immune defense system. As macrophage activation is clearly affected by the surrounding microenvironment, the present study investigated the effect of sulforaphane (SFN) on the bactericidal activity of macrophages and the underlying molecular mechanisms involved in this process. Human THP-1-derived macrophages, primary human peripheral blood mononuclear cell-derived macrophages, and primary mouse bone marrow derived-macrophages (BMdMs) pretreated with SFN or dMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
(53 reference statements)
4
18
0
Order By: Relevance
“…Based on these observations, we hypothesized that the anti-inflammatory effect of SFN can be extended to modulate the overexpression of these target miRNAs in LPS/IFN-γ-stimulated RAW 264.7 macrophages. In line with the study of Deramaudt et al 55 , our findings revealed that SFN significantly downregulated miR-146a levels (Fig. 12 A), which might be explained as dependent-downregulatory negative feedback in response to the SFN inhibitory effect on TLR4 signaling 56 .…”
Section: Discussionsupporting
confidence: 93%
“…Based on these observations, we hypothesized that the anti-inflammatory effect of SFN can be extended to modulate the overexpression of these target miRNAs in LPS/IFN-γ-stimulated RAW 264.7 macrophages. In line with the study of Deramaudt et al 55 , our findings revealed that SFN significantly downregulated miR-146a levels (Fig. 12 A), which might be explained as dependent-downregulatory negative feedback in response to the SFN inhibitory effect on TLR4 signaling 56 .…”
Section: Discussionsupporting
confidence: 93%
“…SFN, as a potent Nrf2 activator, seems a promising therapeutic option for Gram (+) and Gram (−) bacterial infections since it modulates antioxidant and anti-inflammatory responses. Deramaudt et al [ 62 ] studied the intracellular survival of S. aureus in human and mice macrophages treated with SFN. They proposed a mechanism consisting in modulation of p38/JNK signal pathway induced by SFN in macrophages, thus reducing inflammatory response.…”
Section: Mechanisms Of Action Of Sfn On Immune Systemmentioning
confidence: 99%
“…But yet, the detailed mechanism of this observation should be elucidated to define SFN-triggered cellular factors. Deramaudt et al [ 64 ] proposed a combinatory mechanism where reduction of the inflammatory response through modulation of p38 and JNK signaling pathways accompanied antibacterial action of SFN in mice macrophages infected with S. aureus . A similar mode of action may operate in G. mellonella, especially as this organism possesses counterpart MAP kinases, and they are activated in response to infection with the entomopathogenic bacterium Bacillus thuringiensis [ 65 , 66 ] Finally, the dosages chosen for in vivo virulence assay were comparable to those used and reported as safe to treat human diseases.…”
Section: Resultsmentioning
confidence: 99%